THE EFFECTIVENESS OF USING THE SINGING METHOD TO IMPROVE STUDENTS' MASTERY OF ARABIC VOCABULARY AT SDI MIFTAHUL ULUM KRAS - anisatul, eka (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2023)
Arabic language lessons are one of the lessons that many students don't like. There are several factors that make many students not like Arabic language lessons. First, Arabic is a foreign language that is not used when spoken every day. Students speak Indonesian or regional languages. Second, mastery of Arabic vocabulary. Many students do not yet read fluently and master the meaning of Arabic vocabulary. Third, the learning style is boring. This can be caused by teachers who do not use the varied and interesting learning methods that students need. So we need appropriate learning methods that students like. Therefore, researchers use the singing method in learning Arabic so that it can be more easily understood by students. The aim of this research is to describe the application of the singing method in improving students' mastery of Arabic vocabulary. The method used is a descriptive qualitative method. The results of the research show that many students are happy to be able to master Arabic vocabulary using the singing method. Students quickly memorize Arabic vocabulary with song tunes that have been made according to the lesson material. Using the right method will make it easier for teachers and students in the learning process. Keywords: Singing method, Arabic vocabulary, Students